2023
DOI: 10.3390/ijms24032117
|View full text |Cite
|
Sign up to set email alerts
|

Neurons, Nose, and Neurodegenerative Diseases: Olfactory Function and Cognitive Impairment

Abstract: Olfactory capacity declines with aging, but increasing evidence shows that smell dysfunction is one of the early signs of prodromal neurodegenerative diseases such as Alzheimer’s and Parkinson’s disease. The study of olfactory ability and its role in neurodegenerative diseases arouses much interest in the scientific community. In neurology, olfactory impairment is a potential early marker for the onset of neurodegenerative diseases, but the underlying mechanism is poorly understood. The loss of smell is consid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
27
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 144 publications
(157 reference statements)
0
27
0
Order By: Relevance
“…Furthermore, it has bidirectional projections to the prefrontal cortex's anterior/ventral regions (PL/IL) in the medial prefrontal cortex (mPFC), which are associated with olfactory dysfunction in neurodegenerative diseases such as PD and AD. 44 The NBM projects to most sensory cortex regions, including frontal sensorimotor, parietal, temporal, cingulate gyrus, and visual cortex, 69 with a wider range of targets in the sensorimotor cortex, but without a specific pattern. Therefore, the correlation of the Meynert basal ganglion-cortical cholinergic circuit with neurodegenerative diseases is of great significance.…”
Section: Meynert Basal Nucleus-cortical Cholinergic Loopmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it has bidirectional projections to the prefrontal cortex's anterior/ventral regions (PL/IL) in the medial prefrontal cortex (mPFC), which are associated with olfactory dysfunction in neurodegenerative diseases such as PD and AD. 44 The NBM projects to most sensory cortex regions, including frontal sensorimotor, parietal, temporal, cingulate gyrus, and visual cortex, 69 with a wider range of targets in the sensorimotor cortex, but without a specific pattern. Therefore, the correlation of the Meynert basal ganglion-cortical cholinergic circuit with neurodegenerative diseases is of great significance.…”
Section: Meynert Basal Nucleus-cortical Cholinergic Loopmentioning
confidence: 99%
“…demonstrated that the HDB/VDB region is primarily associated with the primary sensory cortex and exhibits specific projections to the primary somatosensory (S1), auditory (A1), and visual (V1) cortical regions based on the distribution of its neck and tail neurons. Furthermore, it has bidirectional projections to the prefrontal cortex's anterior/ventral regions (PL/IL) in the medial prefrontal cortex (mPFC), which are associated with olfactory dysfunction in neurodegenerative diseases such as PD and AD 44 . The NBM projects to most sensory cortex regions, including frontal sensorimotor, parietal, temporal, cingulate gyrus, and visual cortex, 69 with a wider range of targets in the sensorimotor cortex, but without a specific pattern.…”
Section: Meynert Basal Nucleus‐cortical Cholinergic Loopmentioning
confidence: 99%
“…The human olfactory system is responsible for the detection, transmission, and identification of odorous stimuli [ 1 ]. To encode the odors, the olfactory pathways are connected by several circuits, comprising approximately 400 peripheral olfactory receptors, about 10 7 olfactory sensory neurons (OSNs), and central structures, where olfactory information is recognized and stored [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Reprinted from I. Fatuzzo et al [10] a set of primary odors, it is challenging to reproduce the odor we sense [15]. Moreover, it would be impractical to utilize the primary odors with the same number as human olfactory receptors since it is roughly 400.…”
Section: Introductionmentioning
confidence: 99%